Internet Banking Channels and Customer Satisfaction of Nepalese Commercial Banks - Pandey, Bomlal (Dibyajyoti Journal, 2025)
The primary objective of the research is to investigate how Nepalese commercial banks's customers are affected by internet banking channels. Assessing customer satisfaction with internet banking channels and examining the correlation between customer satisfaction and each of the independent variables such as e-banking, mobile banking, ATMs, and points of sale were the specific objectives of the research. Descriptive and causal comparative research designs were used in the study. Customers of Nepalese commercial banks's who use e-banking platforms such internet, mobile, ATM, and point-of-sale banking are the study's target group. To gather answers, the researcher used judgmental sampling. Thus, 18,634 consumers of POS, internet, mobile, and ATM services made up the study's entire population. 400 employees of Nepalese commercial banks made up the study's sample size. Primary sources of information were used in this study. A standardized questionnaire was used to gather primary data from the respondents. The descriptive findings show that, out of the several independent variables, mobile banking has the highest mean score (3.930) with a standard deviation of 0.914. This suggests that mobile banking has a greater effect on client satisfaction. Similarly, customer satisfaction, the dependent variable, has a mean score of 3.840 and a standard deviation of 0.859. The results of the survey also showed that Nepalese commercial banks' mobile banking service considerably increases customer satisfaction. It was found that customers are satisfied with Nepalese commercial banks' mobile banking services. The study also discovered that mobile banking is the primary force behind internet banking channels.